Micro Finance: A Social Innovator - Gupta, Radha (Indian Journal of Finance, 2011)
Solaced people represent the consoled society and it is the consoled society which can give flip to a country’s structural index for its betterment .Our society is comprising of people with different income levels but economic and social interest of the people, especially those who fall in the lower income trap require to be strengthened for that matter. There are different ways to bring innovations for strengthening and transforming their lives by making Mini and Tiny finances available to them and easy access to that is an effective social innovation for making them feel economically and emotionally strong. The present paper is an attempt to highlight how micro finance can bring macro wonders if the real beneficiaries and their problems like poverty can be properly taken care off.